Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di UPT Pajak Jonggol - Hamidah Hadzami; Widhi Ariyo Bimo; Hurriyaturrahman Hurriyaturrahman (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyse the influence of leadership style and the working environment on employee performance at the Jonggol Tax Office. The study was prompted by the low achievement of local tax revenue targets during the 2021–2025 period, which is believed to have been influenced by an ineffective leadership style and a working environment that is not yet conducive. The study employs a quantitative approach using a survey method targeting all employees at the Jonggol Tax Office. Data were collected via a questionnaire and analysed using the SEM-PLS method with the assistance of the SmartPLS application. The results indicate that leadership style and the work environment have a positive and significant influence on employee performance, both partially and simultaneously. The findings confirm that improved employee performance can be achieved through the application of effective leadership styles and the creation of a comfortable and supportive work environment. Therefore, both aspects need to be improved in tandem to support the optimisation of employee performance and theachievement of local tax revenue targets.